2022
DOI: 10.1039/d2nr01387h
|View full text |Cite
|
Sign up to set email alerts
|

A bifunctional GeC/SnSSe heterostructure for highly efficient photocatalysts and photovoltaic devices

Abstract: Alongside highly efficient photocatalysts, high photovoltaic performance is also a key element for efficiently harvesting solar energy. Developing bifunctional materials which satisfy concurrently these two demands is an appealing strategy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…17 Recently, stacking different 2D materials vertically to form van der Waals heterostructures (vdWHs) to achieve more desirable properties has been a hot topic in the 2D material regime. [18][19][20] It has been found that the 2D MoSSe-based vdWHs exhibit exciting novel properties under the influence of the intrinsic electric field of MoSSe. [21][22][23][24] Compared with monolayer MoSSe, multilayer MoSSe has a larger dipole and higher carrier mobility, which are suitable for electronic devices and photocatalysis applications.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, stacking different 2D materials vertically to form van der Waals heterostructures (vdWHs) to achieve more desirable properties has been a hot topic in the 2D material regime. [18][19][20] It has been found that the 2D MoSSe-based vdWHs exhibit exciting novel properties under the influence of the intrinsic electric field of MoSSe. [21][22][23][24] Compared with monolayer MoSSe, multilayer MoSSe has a larger dipole and higher carrier mobility, which are suitable for electronic devices and photocatalysis applications.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested the key role of whewellite as the binder for lignin and cellulose, which distinguished the leaves from other biomasses. Moreover, the electrostatic potential surfaces of the constituents overlapped substantially with each other and showed complementary features, implying strong intermolecular interactions and the formation of local electrostatic fields that can drive charge migration right after excitation 23 . The close-up views (Supplementary Fig.…”
Section: Synthesis and Characterization Of Ammmentioning
confidence: 98%
“…20 The vdWH not only retains the original characteristics of the monolayer but also has the potential to exhibit new physical properties that can be more widely used in the photoelectric field than monolayers. [21][22][23][24] At present, several theoretically calculated heterostructures can be synthesized in the laboratory, suggesting that the new 2D vdWH holds broad prospects for photovoltaic devices, for example, MoS 2 /TiO 2 , 25 MoS 2 /h-BN, 26 WS 2 /graphene, 27 and MoS 2 /SnS 2 . 28,29 In recent years, SnSe 2 can be mechanically exfoliated to obtain 2D monolayers.…”
Section: Introductionmentioning
confidence: 99%